1999
DOI: 10.1093/nar/27.11.2241
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of influenza virus NS1 protein and the human homologue of Staufen in vivo and in vitro

Abstract: A screening for human proteins capable of interacting with influenza virus NS1 has been carried out using the two-hybrid genetic trap in yeast. A cDNA corresponding to the human homologue of Drosophila melanogaster Staufen protein (hStaufen) was isolated that fulfilled all genetic controls of the two-hybrid protocol. Using a hStaufen cDNA isolated from a lambda human library, the interaction of hStaufen and NS1 proteins was characterised in vivo and in vitro. Co-transfection of NS1 cDNA and a partial cDNA of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
80
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 46 publications
7
80
1
Order By: Relevance
“…Expression of neither DRBP76 (35) nor mammalian Staufen (66) prevented IRF7 phosphorylation, nor did they block the inhibitory action of E3L (Fig. 6C and data not shown), despite these proteins being implicated in regulation of PKR and viral infection (35,36,66). Additionally, E3L but not K3L effectively inhibited IRF3 phosphorylation following NDV infection (Fig.…”
Section: Irf7 Phosphorylation Is Blocked By Vaccinia Virus E3l Proteimentioning
confidence: 93%
“…Expression of neither DRBP76 (35) nor mammalian Staufen (66) prevented IRF7 phosphorylation, nor did they block the inhibitory action of E3L (Fig. 6C and data not shown), despite these proteins being implicated in regulation of PKR and viral infection (35,36,66). Additionally, E3L but not K3L effectively inhibited IRF3 phosphorylation following NDV infection (Fig.…”
Section: Irf7 Phosphorylation Is Blocked By Vaccinia Virus E3l Proteimentioning
confidence: 93%
“…By this mechanism, the NS1 protein prevents IFN-␣/␤ synthesis, as well as activation of the antiviral enzyme PKR (23,148,233). It was also suggested that NS1 can inhibit PKR in a dsRNA-independent manner, by forming complexes between the NS1 protein and PKR (348), although direct interaction of NS1 and PKR remains controversial (95). It was recently shown that, through its cellular activator PACT, NS1 can prevent PKR activation (227).…”
Section: Orthomyxovirus: Influenza Virusmentioning
confidence: 99%
“…It is translated from the colinear transcript of segment 8, which also encodes NS2 protein from a spliced mRNA (31, 34). NS1 accumulates in the nucleus early in the infection (4, 32) and when it is expressed from cDNA (26,35,56), but at late times in the infection it is also found in the cytoplasm (49), in association with polysomes (8,16,32).Although NS1 protein is apparently nonessential, as a recombinant virus has been generated that lacks the gene (23), several virus mutants have been isolated or generated which contain mutations in the NS1 protein and are severely hampered for replication (12,14,17,27,28,40,60,(63)(64)(65). The phenotypes of these mutant viruses indicate that NS1 protein may be involved in several steps in the virus infectious cycle, including transcription and/or replication of virus RNA, late virus protein synthesis, and interference with the cellular gene expression, and that it eventually modulates the virulence of virus infections in vivo (2, 23, 68).…”
mentioning
confidence: 99%
“…It is translated from the colinear transcript of segment 8, which also encodes NS2 protein from a spliced mRNA (31,34). NS1 accumulates in the nucleus early in the infection (4,32) and when it is expressed from cDNA (26,35,56), but at late times in the infection it is also found in the cytoplasm (49), in association with polysomes (8,16,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation